The effects of (sulfuric acid concentration, time, temperature) in hydrolysis and (type, weight of yeast) in fermentation process to bioethanol yield in the making of bioethanol from peat - Apriani, Putri; Fitrisyah, Khoirul; Ahmad Roni, Kiagus (International Journal of Engineering and Technology, 2019)
The Indonesian Government's policy regarding the development of alternative energy sources as a substitute for fuel oil has been established bioenergy as an alternative fuel. Bioenergy is energy derived from biofuels. Common biofuel is bioethanol. Bioethanol burning is cleaner than fossil fuels which means reducing greenhouse gas emissions. Therefore, further research is needed on biomass which can be used as raw material for bioethanol production and also the process stages that affect on bioethanol production. The material that can be a substrate for bioethanol production is lignocellulose material. One of the lignocellulosic biomass is peat. This study aims to review the effect of the stages of the process in making bioethanol from peat, namely the delignification process, hydrolysis and fermentation of ethanol produced.Â Â
Keywords: Peat Soil; Delignification; Acid Hydrolysis; Bioethanol.